Measurement of protein flux with positron emission tomography in neonates. Issue 1 (1st January 1999) - Nama, Vijay; Kozlowski, Jim K; Hamvas, Aaron
Abstract : AIM: To determine whether abnormal transvascular protein flux can be measured with positron emission tomography (PET) in neonates with respiratory distress syndrome (RDS). METHODS: Fourteen infants with normal gas exchange (non-RDS group) underwent one PET measurement and 12 infants with RDS (the RDS group) underwent two measurements of protein flux, as determined by the pulmonary transcapillary escape rate for 68 Gallium labelled transferrin (PTCER). RESULTS: The mean PTCER for the RDS infants (132 ± 39 10 -4 /min) was significantly greater than that for infants without RDS (75 ± 27 10 -4 /min). PTCER did not change between measurements in the infants with RDS, including five who received and responded to surfactant replacement between the two scans. CONCLUSIONS: Increased transvascular flux of large molecular weight proteins complicates RDS in preterm infants. PET provides a tool with which to evaluate the processes that contribute to pulmonary dysfunction in neonates.